The triage method: screening alternatives over time with multiobjective decision analysis. (1st January 2014) - Weir, Jeffery D.; Hendrix, Jeremy; Gutman, Alex J.
We present the triage method for screening decision alternatives. Screening reduces a decision maker's time and effort because it removes poor alternatives from unnecessary vetting. We consider the case when alternatives arrive at different times in batch sizes. Alternatives may also 'expire', requiring a decision to be made quickly. A triage function uses a value model to partition incoming alternatives into one of three sets: transferred, rejected, or pending. Pending alternatives are cycled back through the process and are reevaluated against a changing cutoff value. Interval parameters account for uncertainty and disagreements between multiple decision makers. Overall, the triage method provides a dynamic, continuous evaluation of potential alternatives with results that are easily defended and communicated. We illustrate a wartime application of the triage method on proposals seeking funding to defeat improvised explosive devices, the main killer of coalition forces and civilians in Iraq and Afghanistan.